Design and experimental characterization of a reconfigurable transmitarray with reduced focal distance. Issue 3 (17th February 2016) - Di Palma, Luca; Clemente, Antonio; Dussopt, Laurent; Sauleau, Ronan; Potier, Patrick; Pouliguen, Philippe
Abstract : In this contribution, we study the design and experimental characterization of a reconfigurable transmitarray in X-band with reduced focal distance. To this end, we consider an illumination with four feed horn antennas in two different configurations. The focal distance and the horn configuration in the focal plane have been optimized with an in-house simulation tool. The effects of source placement errors and excitation unbalances are also studied. The numerical results show a reduction of the focal distance by a factor 1.8 if compared with the single-source case, for a reconfigurable 400-element transmitarray designed in X-band. Moreover, generation of multiple beams is considered and demonstrated numerically for spatial power combining applications. The experimental results obtained in radiation are in good agreement with the numerical predictions. This multiple-source transmitarray exhibits similar radiation performances as the single-source one in terms of gain, bandwidth and beam tilting capabilities, but with about half its volume. This technique seems very attractive for a better integration on various platforms such as vehicles, drones, aircrafts, buildings, etc.